+0  
 
0
202
1
avatar

e4x-13e2x+12=0

Guest Mar 4, 2015

Best Answer 

 #1
avatar+26412 
+10

$$e^{4x}-13e^{2x}+12=0$$

 

This can be written as:

$$(e^{2x})^2-13e^{2x}+12=0$$

 

which can be written in turn as:

$$(e^{2x}-1)(e^{2x}-12)=0$$

 

So we have:

1.

 $$\\e^{2x}=1\\so\\x=0$$

 

2.

$$\\e^{2x}=12\\\\2x=\ln{12}\\\\x=\frac{\ln{12}}{2}$$

.

Alan  Mar 4, 2015
Sort: 

1+0 Answers

 #1
avatar+26412 
+10
Best Answer

$$e^{4x}-13e^{2x}+12=0$$

 

This can be written as:

$$(e^{2x})^2-13e^{2x}+12=0$$

 

which can be written in turn as:

$$(e^{2x}-1)(e^{2x}-12)=0$$

 

So we have:

1.

 $$\\e^{2x}=1\\so\\x=0$$

 

2.

$$\\e^{2x}=12\\\\2x=\ln{12}\\\\x=\frac{\ln{12}}{2}$$

.

Alan  Mar 4, 2015

14 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details